ANALISIS PENGGUNAAN LABORATORIUM DI SMAN 1 PEMATANG SIANTAR SEBAGAI TEMPAT MELAKUKAN PRAKTIKUM DALAM PEMBELAJARAN BIOLOGI - Jesica Siregar; Mastiur Verawati Silalahi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to determine the using laboratories in improving students' abilities and understanding through in biology learning. The method in this research uses quantitative descriptive methods. Data to measure students' scientific abilities and understanding were obtained from documents, namely laboratory questionnaire data, obtained from one class at SMAN 1 Pematang Siantar. A questionnaire was given to students to obtain data on the effectiveness of laboratory use in terms of students' views and experiences regarding laboratories at school. A laboratory is a certain place or room, etc., which is equipped with equipment for conducting experiments (investigations, etc.). A laboratory is a place to carry out scientific research, experiments, measurements or scientific training. A laboratory is also referred to as a place to carry out practical or research activities which are facilitated by various equipment and supporting laboratory infrastructure. The experimental method is a form of learning that involves students working with objects, materials and laboratory equipment, both individually and in groups.